ANALYSIS OF QUALITY LEARNING URGENCY IN ISLAMIC RELIGIOUS EDUCATION - Mayarisa, Diyah (Journal of Higher Education and Academic Advancement, 2024)
Quality learning is learning that creates an effective and meaningful educational experience for students. Quality learning must be in accordance with the learning objectives that have been set. Every activity or material presented must support the achievement of the learning objectives that have been set. Quality learning should stimulate students to develop problem solving skills. This can be achieved by assigning assignments or projects that require analysis, synthesis, and creative thinking. Quality learning respects students' individual differences. This includes understanding students' learning styles, levels of understanding, and their specific needs, and providing appropriate support. Quality education cannot be cheap, or rather it doesn't have to be cheap or free. However, quality education does not require asking where the money will come from to form all these qualities. The government is obliged to guarantee that every citizen receives an education and guarantees access for the lower classes to quality education. In this way, schools will no longer worry about where the funds will come from, and the community will no longer have difficulty getting access to quality schools with affordable educational costs. Quality learning is an investment in students' personal and academic development. It's not just about relying on a particular method, but also about creating a learning environment that motivates, supports, and encourages students' intellectual and moral growth